Factors affecting the burden among caregivers of epilepsy patients in Hospital Universiti Sains Malaysia - Ahmad, Nik Lili Ariantie (2020)
Background: Epilepsy is a chronic medical problem that needs a proper caregiving process. However, it imposed a great challenge to their caregivers because of many factors. These challenges can be perceived as burden to the caregivers. Later, it may negatively affect in many aspects of life in both patients and their caregivers. Objectives: The aim of this study is to determine the severity of burden among caregivers of epilepsy patients and its associated factors. Method: This cross-sectional study involved caregivers of epilepsy patients in Neurology Clinic, HUSM. All participants were asked to answer questionnaire regarding perceived burden (MZBI), severity of depression (BDI-Malay) and severity of anxiety (BAI-Malay). Result: A total of 116 participants were recruited in this study. Their age ranged from 21 to 78 years old, with the mean age of 44.48 (SD:11.80 years). About two-thirds (68.1%, n=79) of the participants were female and almost all of caregivers were Malay (98.3%, n=114). The mean total score of MZBI was 20.29 (SD: 11.46). About 44.0% (n=51) of caregivers experienced mild to moderate burden. The predictors of caregiver burden were measured using multiple linear regression. The predictors were caregiver depression, caregiver anxiety, caregiver personal income, seizure frequency epilepsy patients with comorbidities. Positive correlations noted between caregiver depression (r=0.299, p-value 0.001), caregiver anxiety (r= 0.333, <0.005) and seizure frequencies (r= 0.263, 0.004) with total score of MZBI. Conclusion: This study shows about half of the caregivers of epilepsy patients has mild to moderate burden. The predictors of caregiver burden were caregiver emotional status (depression and anxiety), caregiver personal income, seizure frequency and epilepsy patients with comorbidities. In future, intervention study, focussing on ways to reduce depression and anxiety among caregivers of epilepsy patients is required to overcome the caregiver burden.